Sol–gel synthesis and solar photocatalytic activity of Ca-alloyed ZnO nanoparticles elaborated using different precursors. Issue 43 (6th July 2020) - Rosset, A.; Djessas, K.; Goetz, V.; Grillo, S.; Plantard, G.
Abstract : Schematic representation of core–shell intrinsic defects in Zn1− x Ca x O nanoparticles observed by EPR spectroscopy. Abstract : Ca-alloyed ZnO nanoparticles elaborated using different calcium precursors (CaSO4, CaCl2, Ca(NO3 )2 and CaCO3 ) at different [Ca]/[Zn] ratios (0, 1, 5, 10, 15 and 20%) have been prepared by a sol–gel method followed by supercritical drying and annealing at 300 °C. The synthesized samples have been characterized by a number of techniques including Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy Dispersive X-ray Spectroscopy (EDS), X-ray Diffraction (XRD), Raman Spectroscopy and Electron Paramagnetic Resonance (EPR). SEM and TEM images reveal that the nanoparticles have a quasi-spherical shape with a grain size between 20 and 40 nm. The EDS results on chemical elementary compositions show that the Ca-alloyed ZnO with a CaCO3 precursor and [Ca]/[Zn] ratios of 5 and 10% are quasi-stoichiometric. The XRD results indicate that all the elaborated nanoparticles have a hexagonal wurtzite structure. Using Raman Spectroscopy a supplementary vibrational mode is detected in the case of CaSO4, CaCO3 and Ca(NO3 )2 precursors. The intrinsic defect centers and defect number have been studied using EPR. Two intrinsic defects with different g factors are identified by EPR for which the spectral intensities change with calcium precursors. Furthermore, EPR reveals a correlation between the defect number and photocatalytic efficiency. The photocatalytic efficiency of the nanoparticles elaborated with different precursors and compositions has been studied for the solar photocatalytic degradation of pyrimethanil, using a solar simulator. The results show that the nanoparticles of Ca-alloyed ZnO elaborated with a CaCO3 precursor give promising results and enhance the photocatalytic efficiency in the solar field.